PENGARUH SUKU BUNGA DAN INFLASI TERHADAP KREDIT INVESTASI INDUSTRI PENGOLAHAN - Hena, Eduardus (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This research aims to determine the effect of interest rates and inflation on processing industry investment credit. The type of data used in this research is secondary data over a period of three years from January 2022 to July 2024. The data comes from the official website of the Indonesian Central Bureau of Statistics (BPS). The data analysis method in this research is multiple linear regression and partial hypothesis testing using the t test and simultaneous testing using the F test. The results of the hypothesis test prove that partially interest rates have no significant effect on processing industry investment credit, while inflation has a negative and significant effect on processing industry investment credit. However, together credit interest rates and inflation have a significant effect on processing industry investment credit. The findings in this research show that processing industry investors do not use interest rates as the main reference for making investment credit in bank financial institutions, especially commercial banks, but use other factors, including inflation, as one of the factors that motivate processing industry investors to make investment credit, namely when If inflation occurs then investment credit decreases and conversely if deflation occurs then investment credit increases according to changes in prices of resources and capital goods purchased for investment. That during inflation, rising prices cause investors to reduce purchases of resources and capital goods used for investment, causing a reduction in processing industry investment credit, conversely there is deflation, so falling prices cause investors to increase purchases of resources and capital goods which are sources of funds for purchases. This is from credit from banks so that there is an increase in processing industry investment credit in banks, especially commercial banks, which is used to increase investment.